OPTIMALISASI PERAN DETASEMEN INTELIJEN DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi Kasus Denintel Kodam Iskandarmuda) - , Alinapia Pasaribu ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is focused on empowering the region's defense through the addition of Regional Military Command (KODIM) units though unconscious will contribute positively to the increased of the region resilience. While the research is oriented to be held on the implementation of Army intelligence functions which are performed by Deninteldam Iskandarmuda in supporting the region of resilience, so that the authenticity aspects of research, in this section will be eligible. This study intends to examine the implementation of policies concerning the function of intelligence, so this research include an applied research, known as policy research, as do the investigation and analysis of a policy that starts from the descriptive, prescriptive to the predictive. The results of this study could be recommended to the policy makers to act in a practical way to resolve policy issues, to be relevant for policy improvements in the future anyway. The obstacles that experienced by Deninteldam Iskandarmuda in carrying out intelligence functions of the Army which is also parts of the implementation of national defense functions, in addition to internal factors (lack of infrastructure, lack of quality and quantity of personnel) as well as external factors. Several external factors that deserve particular attention are still an indication of national disintegration by a group of certain communities, and the persistence of social jealousy in both the stage of implementation of regional autonomy as well as the implementation of regional development in the province including the formation of political or social organizations, as well as budget support inadequate both in cost to perform operations (transportation and procurement of defense equipment associated with the tools to perform intelligence tasks or special communications equipment). The implementation of Deninteldam Iskandarmuda role in implementing the Army intelligence functions such as investigation, security, raising and development unit has been carried out in accordance with the policy direction both of the Commander of Regional Military Command and the Armed Forces Commander of Iskandarmuda, which in this case there is the function of national defense, which in turn affects the resilience of the region.